1999
DOI: 10.1029/1999gl005379
|View full text |Cite
|
Sign up to set email alerts
|

Three‐dimensional velocity structure of the Kilauea Caldera, Hawaii

Abstract: Abstract.High-resolution velocity models (0.5 km resolution) of the Kilauea caldera region are obtained by the tomographic inversion of both P-and S-wave arrival times. Data are from the permanent Hawaiian Volcano Observatory (HVO) seismic network, a broadband seismic network, and a temporary array of stations centered on the southern boundary of the caldera. A low-velocity P-wave anomaly is imaged centered on the southeastern edge of the caldera, with a velocity contrast of about 10% and a volume of 27 km 3. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

16
129
2
4

Year Published

2004
2004
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 110 publications
(151 citation statements)
references
References 19 publications
16
129
2
4
Order By: Relevance
“…Compared with studies on the V p structure, relatively few V p ∕V s models are available. Dawson et al [1999] observed a low-velocity P wave anomaly and corresponding high-V p ∕V s body from 1 km above to 2.5 km below sea level centered on the southeastern edge of the caldera, which was interpreted as a densely cracked body containing partial melt. We also observe a low-P velocity body between 1.6 and 3.6 km depth.…”
Section: Comparison With Previous Studiesmentioning
confidence: 97%
See 3 more Smart Citations
“…Compared with studies on the V p structure, relatively few V p ∕V s models are available. Dawson et al [1999] observed a low-velocity P wave anomaly and corresponding high-V p ∕V s body from 1 km above to 2.5 km below sea level centered on the southeastern edge of the caldera, which was interpreted as a densely cracked body containing partial melt. We also observe a low-P velocity body between 1.6 and 3.6 km depth.…”
Section: Comparison With Previous Studiesmentioning
confidence: 97%
“…Refraction studies initially helped to resolve crustal structure [e.g., Ryall and Bennett, 1968;Hill, 1969]. The first three-dimensional (3-D) seismic velocity model for Kilauea was obtained by inverting teleseismic data [Ellsworth and Koyanagi, 1977] and was followed by numerous local tomographic studies [e.g., Thurber, 1984;Rowan and Clayton, 1993;Okubo et al, 1997;Dawson et al, 1999;Haslinger et al, 2001;Hansen et al, 2004;Monteiller et al, 2005;Park et al, 2007;Got et al, 2008;Park et al, 2009;Syracuse et al, 2010]. The majority of these studies focus on the compressional (P) wave velocity structure near Kilauea volcano.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…To find a source location for a given time window, a three-dimensional grid of assumed source locations is defined and travel times from every node in the grid to every receiver in the network are computed. The velocity model is considered to be homogenous and reflects the average shallow velocity structure of Kilauea derived by Dawson et al [1999]. The travel times are then used to define time-offsets for each receiver in the time window, and a three dimensional volume of radial semblance is calculated using Almendros and Chouet [2003, equation (9)].…”
Section: Introductionmentioning
confidence: 99%